An Animal Model of Abacavir-Induced HLA-Mediated Liver Injury. (8th January 2018) - Song, Binbin; Aoki, Shigeki; Liu, Cong; Susukida, Takeshi; Ito, Kousei
Abstract: Genome-wide association studies indicate that several idiosyncratic adverse drug reactions are highly associated with specific human leukocyte antigen (HLA) alleles. For instance, abacavir, a human immunodeficiency virus reverse transcriptase inhibitor, induces multiorgan toxicity exclusively in patients carrying the HLA-B*57:01 allele. However, the underlying mechanism is unclear due to a lack of appropriate animal models. Previously, we developed HLA-B*57:01 transgenic mice and found that topical application of abacavir to the ears induced proliferation of CD8 + lymphocytes in local lymph nodes. Here, we attempted to reproduce abacavir-induced liver injury in these mice. However, oral administration of abacavir alone to HLA-B*57:01 transgenic mice did not increase levels of the liver injury marker alanine aminotransferase. Considering the importance of innate immune activation in mouse liver, we treated mice with CpG oligodeoxynucleotide, a toll-like receptor 9 agonist, plus abacavir. This resulted in a marked increase in alanine aminotransferase, pathological changes in liver, increased numbers of activated CD8 + T cells, and tissue infiltration by immune cells exclusively in HLA-B*57:01 transgenic mice. These results indicate that CpG oligodeoxynucleotide-induced inflammatory reactions and/or innate immune activation are necessary for abacavir-induced HLA-mediated liver injury characterized by infiltration of CD8 + T cells. Thus, we developed the first mouse model of HLA-mediated abacavir-induced idiosyncratic liver injury. Further investigation will show that the proposed HLA-mediated liver injury model can be applied to other combinations of drugs and HLA types, thereby improving drug development and contributing to the development of personalized medicine.